Reinvestigation on polarization and strain response of electrically poled lead titanate zirconate ceramics under low-to-medium electric field loading - Dong, Wanjing; Hui, Tong; Zhengyi, Liu (Materials research express, 2020)
The polarization and strain response of electrically poled lead zirconate titanate ceramics was reinvestigated under low-to-medium electric field loading. A phenomenon that is usually ignored was pointed out and discussed. That is, under low-to-medium cyclic electric field loading, remnant strains measured under a negative electric field loading are larger than those measured under a positive electric field loading. Here, ‘positive’ and ‘negative’ mean that the applied electric field is aligned or antiparallel to the pre-poling direction of the material, respectively. Moreover, a reverse trend was observed for remnant polarizations. Texture-dependent domain switching, defect dipole reorientation, and interactions between them were used to rationalize this phenomenon. In addition, the equation S = d init + α E 0 ⁎ E ± α 2 E 0 2 − E 2 , which is used to describe the strain response, was modified by taking the asymmetry of the electric field versus strain curve into consideration. The modified equation can better describe the strain response than the original equation.